Avaliação da solução sólida Ca3-xBaxZrSi2O9 para aplicação em dispositivos de micro-ondas e radiofrequência - Chaves, Anderson Valério (2023)
The present study aims to evaluate the Ca3ZrSi2O9 (CZS) phase and its resulting solid solution with the addition of barium for use in electronic devices. The samples were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and scanning electron microscopy (SEM) for morphological analysis. The results indicated the formation of a single phase, confirmed the assignment of characteristic bands related to the CZS structure bonds, and the micrographs showed the presence of granular and condensed pores. Dielectric measurements of CZS in the radiofrequency range were performed using Impedance Spectroscopy, where no phase transition was observed. For the microwave range, the dielectric permittivity values of 11.80, dielectric loss of 8.28 x 10–4, and resonant frequency temperature coefficient (τf) of –44.30 ppm °C–1 were obtained for the pure phase. Additionally, the use of this material as a dielectric resonator antenna (DRA) at 6.57 GHz was proposed. The addition of barium was evaluated in the solid solution Ca3-xBaxZrSi2O9 (x = 0.15, 0.30, and 0.45), referred to as 0.15BaCZS, 0.30BaCZS, and 0.45BaCZS, respectively. Structural and morphological characterizations indicated the presence of a crystalline majority phase of CZS and a minority phase of BaZrO3, along with characteristic bands associated with the CZS sample. Preliminary microwave tests showed that the dielectric losses and permittivity varied with increasing barium proportion in the solid solution composition, as well as the τf. For the DRA tests, the samples operated below –10 dB within the frequency range of 6.57 to 7.7 GHz, behaving as materials suitable for microwave devices for applications in the C-band.